Jihadist propaganda as a threat indicator: the case of Spain - Torres-Soriano, Manuel Ricardo (Terrorism and political violence, 2020)
The present article examines the relevance of jihadist propaganda as an indicator of the threat from terrorism. To that end, it uses jihadist propaganda output referring to Spain as a case study. It proposes an instrument of measurement based on content analysis, in which the origin, format, content, and distribution method of the materials are taken as categories. The results offer empirical evidence regarding the seriousness of the terrorist threat against Spain, a country that is particularly exposed due to its historical and geographical singularities and its status as the victim of an attack deemed paradigmatic in the minds of jihadists.